Оценка эффективности методов повышения сопротивления усталости сварных соединений при ударном нагружении в условиях низкой температуры - Дегтярев, В.А.; Шульгинов, Б.С. (Проблемы прочности, 2000)
Проанализированы экспериментальные данные по влиянию различных упрочняющих обработок (механическое снятие усиления шва, аргонодуговая, взрывом, ультразвуковой поверхностный наклеп) на сопротивление усталости сварных соединений низколегированных сталей при гармоническом и ударном нагружении в условиях комнатной и низкой (-60°С) температур. Установлено количественное повышение сопротивления усталости при каждом виде обработки в одинаковых условиях испытаний. Сравнение эффективности каждого вида обработки в условиях ударного нагружения при низкой температуре относительно исходного состояния сварного соединения при гармоническом нагружении и комнатной температуре показало, что наиболее целесообразно использовать ультразвуковой поверхностный наклеп для упрочнения сварных конструкций, эксплуатируемых в условиях низких климатических температур. We performed the comparative analysis of experimental data on the influence of various material strengthening treatments (mechanical removal of the welding seam reinforcement, argon-ark treatment, explosion, ultrasonic surface work-hardening) on the fatigue strength of welded joints of low-carbon steels under harmonic and impact loadings at the room and low (-60°С) temperatures. We obtained quantitative results on the improvement of fatigue strength characteristics for each type of treatment under the identical test conditions. Comparison of the efficiencies of each type of treatment under impact loading conditions at low temperature in reference to the initial welded joint condition under room-temperature harmonic loading has shown that ultrasonic surface work-hardening is most expedient for strengthening of welded structures operating under low-temperature conditions. We performed the comparative analysis of experimental data on the influence of various material strengthening treatments (mechanical removal of the welding seam reinforcement, argon-ark treatment, explosion, ultrasonic surface work-hardening) on the fatigue strength of welded joints of low-carbon steels under harmonic and impact loadings at the room and low (-60°С) temperatures. We obtained quantitative results on the improvement of fatigue strength characteristics for each type of treatment under the identical test conditions. Comparison of the efficiencies of each type of treatment under impact loading conditions at low temperature in reference to the initial welded joint condition under room-temperature harmonic loading has shown that ultrasonic surface work-hardening is most expedient for strengthening of welded structures operating under low-temperature conditions.